Scrotal Scintigraphy in Testicular Torsion: An Experience at a Tertiary Care Centre - O, Saleh; MS, El-Sharkawi; MB, Imran (IIUM Medical Journal Malaysia, 2012)
Introduction: Accurate diagnosis of testicular torsion is important to avoid serious consequences of any delay in proper management. Objective of this study was to compare performance parameters of scrotal scintigraphy and scrotal ultrasound to correctly and confidently diagnose the etiology of an acute scrotum in university hospital settings. Materials and Methods: This is an observational study with a retrospective analysis of data from July 2004 to March 2009. A total of 21 patients (age three years to 37 years) were referred from Emergency Department for scrotal scintigraphy to rule out testicular torsion. All patients went through a standard protocol for scrotal scintigraphy upon referral to Nuclear Medicine Department. Scrotal ultrasound was performed either before or immediately after the scintigraphy. Results: Confirmation of the diagnosis in all 21 patients was based either on the histopathological report of the surgical specimen (n=7) or through clinical follow up (for conservative treatment; n=14). At presentation, nine patients (43%) had left sided pain, and 12 patients (57%) had right sided pain (p>0.05). Eight patients (38%) were diagnosed to have testicular torsion on scintigraphy; one of them turned out to be false positive (testicular abscess). Sensitivity of scrotal scintigraphy to diagnose testicular torsion was 100%, specificity 93%, negative predictive value (NPV) 100% and positive predictive value (PPV) 88%. Conclusion: Scrotal scintigraphy in an acute scrotum is a feasible procedure to be performed on emergency basis, and it is a valid and reliable test to diagnose testicular torsion when US is doubtful or non conclusive.